Former of Turn Trajectory of Sliding Valve Shaft of Gas Line; MATEC Web of Conferences; Vol. 91 : Smart Grids 2017 - Dementyev V. Yu. Vladislav; Gusev N. V. Nikolay Vladimirovich; Koyain N. V. Nikolay Vadimovich; Shiryaev S. Yu. Sergey (2017, 2017)
Title screen